2011
DOI: 10.1016/j.chembiol.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

HSF1-Dependent Upregulation of Hsp70 by Sulfhydryl-Reactive Inducers of the KEAP1/NRF2/ARE Pathway

Abstract: SUMMARY The KEAP1/NRF2/ARE pathway and the heat shock response are inducible cytoprotective systems regulated by transcription factors NRF2 and HSF1, respectively. We report that structurally distinct small molecule NRF2 activators, all of which react with sulfhydryl groups but differ in potency by 15,000-fold, upregulate Hsp70, a prototypic HSF1-dependent gene. Hsp70 upregulation requires HSF1 but is NRF2 independent. We further demonstrate that a sulfoxythiocarbamate inducer conjugates to the negative regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 23 publications
7
107
0
Order By: Relevance
“…Here, we observed that Aβ-depleted GSH, an indicator of oxidative stress, caused a mild increase in Hsp90 and Hsp70 levels. It is tempting to speculate that the mild increase of level of Hsps in Aβ-injected group may be due to previously described reactive oxygen species-induced dissociation and the activation of HSF-1 (Zhang et al 2011). GA pretreatment increased Hsp70 more significantly along with modulation of Hsp90 hippocampal level.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed that Aβ-depleted GSH, an indicator of oxidative stress, caused a mild increase in Hsp90 and Hsp70 levels. It is tempting to speculate that the mild increase of level of Hsps in Aβ-injected group may be due to previously described reactive oxygen species-induced dissociation and the activation of HSF-1 (Zhang et al 2011). GA pretreatment increased Hsp70 more significantly along with modulation of Hsp90 hippocampal level.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that TBE-31, at nanomolar concentrations, protects cells against peroxynitrite toxicity and showed the essential requirement for Nrf2 for protection (46). We next asked whether TBE-31 could protect cells with 6-TG in their genomic DNA against oxidative stress caused by UVA radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The differential concentration dependence of the two responses suggests that activation of Nrf2 precedes that of Hsf1: The Keap1/Nrf2/ARE pathway is at the forefront of cellular defense, protecting against instant danger; the HSR closely follows to resolve subsequent potentially devastating damage, saving the proteome. This concept could have positive consequences for the treatment of renal inflammatory pathologies and related diseases (Zhang et al 2011). …”
Section: Hsp70/no Renal Cytoprotective Action As Consequence Of Statimentioning
confidence: 99%